2013
DOI: 10.1080/00140139.2013.821172
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Cognitive Failures Questionnaire

Abstract: Ergonomists have long been interested in human error and the role of high work demands due to poor equipment design and excessive workload. The CFQ measures attentiveness in daily life and is shown to have excellent psychometric properties that make it suitable for use in both laboratory and field studies as a trait measure of attentiveness in daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 30 publications
8
119
1
1
Order By: Relevance
“…When looked at the validity scores, CFQ and TAI scores had found positive correlations same as another researches (7,14,28,29). Sullivan and Payne (2007) stated that the relationship between cognitive failures, anxiety, and psychological tension (29).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…When looked at the validity scores, CFQ and TAI scores had found positive correlations same as another researches (7,14,28,29). Sullivan and Payne (2007) stated that the relationship between cognitive failures, anxiety, and psychological tension (29).…”
Section: Discussionsupporting
confidence: 64%
“…We participated another researcher in high test-retest reliability of the CFQ is really a reflection of a constant cognitive load at school/ work etc. and not a measure of a stable personality trait (7,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single factor model was only marginally worse: CFI = .84, RMSEA = .07. But Bridger et al (2013) found that Cronbach's alpha was .92, which is evidence of high internal consistency for a unidimensional construct. These investigators also reported a test-retest reliability of .71 over two years, which suggests a human characteristic that is fairly stable over time.…”
Section: The Dimensionality Of the Cognitive Failures Questionnairementioning
confidence: 97%
“…Originally it 224 was claimed that the scale measured a unitary construct, with specific subfactors varying between 225 populations (Broadbent et al, 1982). Subsequent studies have found that multi-factor solutions fit the 226 data better than single-factor solutions (Bridger et al, 2013;Wallace, 2004); however, the specific 227 factor structure varies between populations and even within populations over time (Bridger et al, 228 2013). Given this inconsistency, and the fact that overall CFQ scores are significantly associated 229 with some aspects of visual attention (e.g., Forster and Lavie, 2007), for the current study overall 230 CFQ scores were analysed.…”
Section: Self-report Measures 211mentioning
confidence: 99%